Critical thinking and communication : - Inch, Edward S. (Pearson Education, 2015)
Critical Thinking and Communication, 7/e, encourages students to develop skills in constructing and refuting arguments in contexts ranging from informal conversations to structured debates. The authors stress the importance of argumentation in everyday life while building student competence and critical awareness. Through exercises and examples, students learn to create arguments and develop, understand, and interpret extended cases.